Differentiated Instruction in Mixed-Ability Classrooms: Experiences of Special Education Teachers - Patel, Daniel; Kim, Nora (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aims to explore the experiences of special education teachers in implementing differentiated instruction (DI) within mixed-ability classrooms. This qualitative research utilized a phenomenological approach to gain in-depth insights into the participants’ experiences. Data were collected through semi-structured interviews with 25 special education teachers from various schools in a metropolitan area. Participants were selected through purposive sampling to ensure they had significant experience with DI. The interviews, each lasting 60 to 90 minutes, were transcribed verbatim and analyzed using thematic analysis. The data collection continued until theoretical saturation was achieved, ensuring a comprehensive understanding of the teachers’ experiences. The analysis revealed three main themes: challenges in differentiated instruction, strategies for effective differentiation, and perceived effectiveness and outcomes. Teachers reported significant challenges, including resource limitations, managing student diversity, assessment difficulties, increased workload, and issues with parental involvement. To address these challenges, teachers employed strategies such as flexible grouping, curriculum adaptation, professional development, collaborative planning, and enhancing student engagement. The perceived effectiveness of DI included improved student progress, positive changes in classroom dynamics, increased teacher satisfaction, and greater inclusivity. Differentiated instruction is a vital approach in mixed-ability classrooms, promoting equitable learning opportunities for all students. Despite the challenges, the strategic implementation of DI leads to significant positive outcomes in student performance and classroom inclusivity. Schools should support teachers through professional development, adequate resources, and collaborative opportunities to enhance the effectiveness of DI. Further research should focus on larger, diverse samples and mixed-methods approaches to provide a more comprehensive understanding of DI practices.